2015
DOI: 10.1080/15384101.2015.1053664
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase regulatory subunit 1 promotes cell proliferation by insulin regulation

Abstract: These authors contributed equally to this work.Keywords: body size, cell proliferation, CKS1, insulin, midgut Cyclin-dependent kinase regulatory subunit 1 (CKS1) helps regulate the cell cycle to increase cell number. However, the hormonal regulation on CKS1 expression is not well understood. We report that CKS1 is involved in the promotion of cell proliferation with insulin regulation in the lepidopteran insect Helicoverpa armigera. CKS1 is expressed in various tissues during the larval feeding stage. CKS1 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The lack of a juvenile hormoneproducing organ, the corpora allata, elevates FoxO activity and results in small pupae . Higher concentrations of 20E repress insulin-induced gene expression in H. armigera (Liu et al, 2015). In Drosophila, FoxO interacts with USP to mediate ecdysone biosynthesis .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a juvenile hormoneproducing organ, the corpora allata, elevates FoxO activity and results in small pupae . Higher concentrations of 20E repress insulin-induced gene expression in H. armigera (Liu et al, 2015). In Drosophila, FoxO interacts with USP to mediate ecdysone biosynthesis .…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila melanogaster, 20E also stops stem cell proliferation (10). In Helicoverpa armigera, 20E causes a switch from autophagy to apoptosis (11), counteracts the action of insulin (12), promotes phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase (PTEN) expression (13), and promotes the Hippo pathway to induce apoptosis (14). Furthermore, 20E is used as a food additive to maintain the glucose-lipid balance in humans, without the side effects of mammalian hormones (15).…”
mentioning
confidence: 99%
“…Our study also showed that nuclear-located Yki prevents apoptosis and upregulates IAP1 expression. A previous study indicated that the H. armigera larval midgut cells are proliferating at the sixth instar 48-h stage but undergo apoptosis at the sixth instar 96-h stage (18). Therefore, the knockdown of Yki in sixth instar 6-h larvae would block cell proliferation, accelerating the 20E-mediated midgut apoptosis and larval-pupal transition.…”
Section: Discussionmentioning
confidence: 96%